2021
DOI: 10.3390/cancers13071553
|View full text |Cite
|
Sign up to set email alerts
|

Impact on All-Cause and Cardiovascular Mortality Rates of Coronary Artery Calcifications Detected during Organized, Low-Dose, Computed-Tomography Screening for Lung Cancer: Systematic Literature Review and Meta-Analysis

Abstract: Although organized, low-dose, computed-tomography (CT) scan lung-cancer screening has been shown to lower all-cause and lung-cancer-specific mortality, the primary cause of death for subjects eligible for such screening remains cardiovascular (CV) mortality. This meta-analysis study was undertaken to evaluate the impact of screening-scan-detected coronary artery calcifications (CACs) on CV and all-cause mortality. We conducted a systematic review and meta-analysis of studies reporting CV mortality according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…The automated AI-driven analysis of coronary artery calcifications of MILD volunteers confirmed our previous observation that CAC is an independent predictor for all-cause mortality (3), and that CAC > 400 is associated with a significantly worse survival at 12 years. These results are in keeping with a case-cohort study from the NELSON trial demonstrating that higher strata of CAC score had a significantly higher risk of coronary events compared with negative (10), and with a meta-analysis of 6 LCS trials showing that subjects with high CAC values had more than two-fold increased relative risk of all-cause mortality (11). The extended follow-up of MILD trial revealed a 3-fold higher mortality risk for aCAC >20 and 5-fold risk for aCAC >400 (p<0.0001 and p<0.0001 respectively).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The automated AI-driven analysis of coronary artery calcifications of MILD volunteers confirmed our previous observation that CAC is an independent predictor for all-cause mortality (3), and that CAC > 400 is associated with a significantly worse survival at 12 years. These results are in keeping with a case-cohort study from the NELSON trial demonstrating that higher strata of CAC score had a significantly higher risk of coronary events compared with negative (10), and with a meta-analysis of 6 LCS trials showing that subjects with high CAC values had more than two-fold increased relative risk of all-cause mortality (11). The extended follow-up of MILD trial revealed a 3-fold higher mortality risk for aCAC >20 and 5-fold risk for aCAC >400 (p<0.0001 and p<0.0001 respectively).…”
Section: Discussionsupporting
confidence: 85%
“…Coronary artery calcium (CAC) is an independent predictor of cardiovascular (CV) events (1). Previous studies in low dose computed tomography (LDCT) screening participants demonstrated the predictive value of CAC score for all-cause and CV mortality (2,3), with a CAC scoring accuracy of LDCT that was similar to the one achieved by electrocardiographic-gated cardiac CT (4,5).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…For instance, every 1% increase in the percentage of %LAA independently predicted all-cause death in the CT arm of the National Lung Screening Trial (NLST) 26 . In a recent meta-analysis including studies from different LCS trials, subjects in high CAC categories had a relative risk of all-cause mortality of 2.47 (95% CI, 1.75-3.47) and 2.90 (95% CI, 1.57-5.36) based on a fixed-effect model and a random-effect model, respectively 31 . In keeping with these results, our findings argue in favor of %LAA and CAC to predict all-cause and noncancer mortality in LCS.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery calcium (CAC) is an independent predictor of cardiovascular (CV) events and mortality [ 1 ]. Previous studies in low-dose computed tomography (LDCT) lung cancer screening (LCS) participants demonstrated the predictive value of manual CAC scoring [ 2 , 3 ]. Nevertheless, the timely consuming procedure of manually computing CAC scoring currently hinders its routine evaluation in LCS.…”
Section: Introductionmentioning
confidence: 99%